URGENSI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI - Aji Silmi, Thoriq; Hamid, Abdulloh (Inspiratif Pendidikan, 2023)
THE URGENCY OF USING TECHNOLOGY-BASED LEARNING MEDIA. The progress of the times has become a conversation every day, and has become a new habit in life. Technology plays a role in relation to the progress of the times, developments have spread to all sectors, including the education sector. In the learning process, the use of effective and efficient media to improve the quality and competence of students in order to be able to achieve learning objectives is very necessary. Various learning media provide flexibility for educators to design learning according to the characteristics of students. The presence of this technology-based learning media gives a new color and style to the world of education. With the technology that enters the world of education, it is expected to be able to change conventional habits towards modernization. In this study, several concrete facts are presented regarding the use of technology-based learning media so that they can be used in educational institutions in each educational unit, following the learning styles and characteristics of students. Where this learning has an important role in the order of human life, and as an alternative to an image and sound-based media to convey learning material.